Endothelial Function Is Associated with White Matter Microstructure and Executive Function in Older Adults - Johnson, Nathan F.; Gold, Brian T.; Brown, Christopher A.; Anggelis, Emily F.; Bailey, Alison L.; Clasey, Jody L.; Powell, David K. (Frontiers in Aging Neuroscience, 2017)
Age-related declines in endothelial function can lead to cognitive decline. However, little is known about the relationships between endothelial function and specific neurocognitive functions. This study explored the relationship between measures of endothelial function (reactive hyperemia index; RHI), white matter (WM) health (fractional anisotropy; FA, and white matter hyperintensity volume; WMH), and executive function (Trail Making Test; Trail B – Trail A). Participants were 36 older adults between the ages of 59 and 69 (mean age = 63.89 years, SD = 2.94). WMH volume showed no relationship with RHI or executive function. However, there was a positive relationship between RHI and FA in the genu and body of the corpus callosum. In addition, higher RHI and FA were each associated with better executive task performance. Tractography was used to localize the WM tracts associated with RHI to specific portions of cortex. Results indicated that the RHI-FA relationship observed in the corpus callosum primarily involved tracts interconnecting frontal regions, including the superior frontal gyrus and frontopolar cortex, linked with executive function. These findings suggest that superior endothelial function may help to attenuate age-related declines in WM microstructure in portions of the corpus callosum that interconnect prefrontal brain regions involved in executive function.